Danos na copa : crescimento, produção e desbaste em povoamentos clonais e seminais de Teca em duas regiões de Mato Grosso - Gava, Fernando Henrique (2015)
The objective of this research was evaluate the development of clonal and seminal plants of Teak associated with crown damage intensities in two regions in southwest Mato Grosso. The study was conduct in Figueirópolis D’Oeste and Lambari D’Oeste with clones proceeding from Perlis, Malaysia and Solomon Islands and seminal plants from studies refions. Treatments were structured in a randomized block design, with measuring circumference at breast height, commercial and total heights in permanent plots to six and seven years old. In addition, the cubed, the stem analysis and quantified the frequency of broken cup have been made. For the full set of data and separated by broken crown and crown without damage, models were tested for relative hipsometric. With collected data were simulated selective thinning 40% intensity of the trees, determinating volumes, increases in height, CBH and plantation volume, in addition the volume extracted by the thinning. In both regions, the clones were more affected by crown damage in relation to seminal plants. The crown damage affects the hypsometric relation and tested models are not suitable to estimate the height. In Lambari D'Oeste, for clones 62 and 68 and seminal plants, the average length of crown damage to the sixth year, was higher than the average increase recorded in the seventh year. In both regions, the clone 61 stood out for the estimated thinning volume and Lambari D'Oeste clone 62 was statistically equal to 61. In Figueirópolis D'Oeste, clones of Perlis were higher than in Solomon Islands, and both regions the least volume of thinning was produced by the seminal plants.